Silicon Valley. The complete fourth season [videorecording (DVD)] - Middleditch, Thomas; Brener, Josh; Miller, T. J., 1981-; Starr, Martin, 1982- (HBO Home Box Office, 2017)
In the high-tech gold rush of modern Silicon Valley, the people most qualified to succeed are the least capable of handling success. A comedy partially inspired by Mike Judge's own experiences as a Silicon Valley engineer in the late 1980s.